Cerebral Tuberculoma of Right Frontal Lobe in an Unconscious Patient - Roka, Yam Bahadur; Roka, Narayani (Journal of Nepal Health Research Council, 2020)
Cerebral tuberculoma of the brain are uncommon presentation of tuberculosis (1%). A 17-year female presented to the emergency with a Glasgow Coma Score of (eye-1, verbal-1 and motor-3), 5/15 bilateral fixed pupils with laborious breathing. The radiological features were suggestive of aintracerebral abscess/ glioma. Intraoperatively the brain was very tense and a large, vascular, mass was present that was excised completely. Her histopathology revealed features of tuberculoma and she was started on anti-tubercular treatment. She is discharged home with regular follow-up for the last 10 months.Cerebral tuberculoma although uncommon should be thought of in developing countries as differential of cystic enhancing lesions of the brain.Keywords: Abscess; central nervous system; glioma; tuberculoma; tuberculosis